Analisa Koordinasi Proteksi Over Current Relay pada Gardu Induk Bangil - Wahyu Hendra Prasetya; Misbahul Munir; Novian Patria Uman Putra; Nasyith Hananur Rohiem; Ilmiatul Masfufiah (Institut Teknologi Adhi Tama Surabaya, 2022)
A reliable protection system is tasked with tracking and finding faults quickly so that it can quickly isolate the disturbed system so that it does not interfere with the system above it. The protection system can be said to be reliable if when the disturbance is in progress, the closest cb will immediately work and cut off the electricity so as not to interfere with other systems. Therefore, a coordination system is needed, namely the Overcurrent Relay on the Pandaan and Sukorejo feeder channel reclosers. The coordination of this protection system is intended so that, when one of the BUS is disturbed, this system will feel an imbalance that causes the continuity of power flow to be disrupted, so it is necessary to set overcurrent relays in order to obtain good settings and electrical equipment can be avoided from all kinds of damage. After calculating and correcting the Over Current Relay setting on the Pickup Current and Time Dial values, the new settings applied have worked according to their respective functions when a disturbance occurs. The T value used from the closest to the load is 0.3, then 0.5 seconds, and the far end with the load is 0.9, then 1.1 seconds